Desain Konsep Inovasi Perahu Wisata Panorama Bawah Air Lobang Buaya, Pantai Namanalu-Negeri Morella - Siahainenia, Reico H. (ARIKA, 2025)
Tourists who enjoy the panoramic beauty of the underwater Namanalu beach, "Lobang Buaya" from a traditional boat are disturbed by problems: refraction of vision, reflection of sunlight into the eyes, and protection against heat and rain. The tour boat transportation service sales group wants to overcome this problem and even intends to provide night tour services. Research using this quantitative descriptive method has revealed the concept of innovative design as a solution to the problem of traditional boats, tourism facilities. Panoramic boxes and boat roofs are a solution to the problem of refraction of views, reflections and protection of tourists against rain and heat, while the underwater lighting system is a solution for opportunities for tourist services at night.